Insights Into the Known 13C Depletion of Methane—Contribution of the Kinetic Isotope Effects on the Serine Hydroxymethyltransferase Reaction - Gleixner, Gerd (Frontiers in Chemistry, 2022)
We determined the kinetic isotope effect on the serine hydroxymethyltransferase reaction (SHMT), which provides important C1 metabolites that are essential for the biosynthesis of DNA bases, O-methyl groups of lignin and methane. An isotope effect on the SHMT reaction was suggested being responsible for the well-known isotopic depletion of methane. Using the cytosolic SHMT from pig liver, we measured the natural carbon isotope ratios of both atoms involved in the bond splitting by chemical degradation of the remaining serine before and after partial turnover. The kinetic isotope effect 13(VMax/Km) was 0.994 ± 0.006, and 0.995 ± 0.007 on position C-3 and C-2, respectively. The results indicated that the SHMT reaction does not contribute to the 13C depletion observed for methyl groups in natural products and methane. However, from the isotopic pattern of caffeine, isotope effects on the methionine synthetase reaction and on reactions forming Grignard compounds, the involved formation and fission of metal organic bonds are likely responsible for the observed general depletion of “activated” methyl groups. As metal organic bond formations in methyl transferases are also rate limiting in the formation of methane, they may likely be the origin of the known 13C depletion in methane.